(3GdJShjb fXQjGJ MOjKIs - (3OjaO(B, (3HjHds ((3YeGf(B:s (3OGQ GdGgdjI ddfTQ(B,s, 2007)
(3SHY NWhGJ dcJGHI NWhI GdJShjb aj jhe hGMO , cja JYQa GdYeQ GdGaJQGVj dRHhfc , EeG Cf JejR Yedc Ch SJNSQ , NeS NWhGJ dNdb QSGdJc GdJShjbjI cja JLYd GdGMGdGJ JgWd cGdeWQ , GdJQcjR Ydi eQcR GdbhI (B... (3RHGFfc , cja JDKQ Ydi RHGFfc , GdJShjb GdeTJQc , eGgh GdfTGW GdJLGQj GdPj JYed Hg , cja JSJWjY GdCTjGA GdebOeI eLGfG Cf JRjO ef GjQGOJc , GdJShjb HGdVeGf , GdJShjb aj GdHjFI GdedGFeI , GSJNOGe HMK GdShb dGYOGO GSJQGJjLjGJ JShjb eHcQI YfUQG ddGYdGf GdfGLM ddfTGW GdJLGQj GdUZjQ NWhI dGYOGO GdfehPL QSGdI eHjYGJ , GSJQGJLjI fLGM GdgGJa aj GdfTGWGJ GdUZjQI , cja JSYQ efJLc Ch NOeJc dJMUd Ydi Ydi QHM , eVGYaI GdeHjYGJ , GdJShjb GdeHGTQ ddfTGWGJ GdJLGQjI GdUZjQI , GdeaJGM GdSMQj ddeHjYGJ GdeJcQQI GdeVehfI GdCShGb GdNjQjI CSQGQ GdTgQI GdeLGfjI (B.s
Keywords: (3COGQI GdeHjYGJs; (3GdJShjb(B-(3NWWs; (3JShjbs